Red and processed meat consumption and purchasing behaviours and attitudes: impacts for human health, animal welfare and environmental sustainability - Clonan, Angie; Wilson, Paul; Swift, Judy A.; Leibovici, Didier; Holdsworth, Michelle (Cambridge University Press, 2015)
Objective: Higher intakes of red and processed meat are associated with poorer health outcomes and negative environmental impacts. Drawing upon a population survey the present paper investigates meat consumption behaviours, exploring perceived impacts for human health, animal welfare and the environment. Design: Structured self-completion postal survey relating to red and processed meat, capturing data on attitudes, sustainable meat purchasing behaviour, red and processed meat intake, plus sociodemographic characteristics of respondents. Setting: Urban and rural districts of Nottinghamshire, East Midlands, UK, drawn from the electoral register. Subjects: UK adults (n 842) aged 18–91 years, 497 females and 345 males, representing a 35·6 % response rate from 2500 randomly selected residents. Results: Women were significantly more likely (P <0·01) to consume≤1 portion of meat/d compared with men. Females and older respondents (>60 years) were more likely to hold positive attitudes towards animal welfare (P<0·01). Less than a fifth (18·4 %) of the sample agreed that the impact of climate change could be reduced by consuming less meat, dairy products and eggs. Positive attitudes towards animal welfare were associated with consuming less meat and a greater frequency of ‘higher welfare’ meat purchases. Conclusions: Human health and animal welfare are more common motivations to avoid red and processed meat than environmental sustainability. Policy makers, nutritionists and health professionals need to increase the public’s awareness of the environmental impact of eating red and processed meat. A first step could be to ensure that dietary guidelines integrate the nutritional, animal welfare and environmental components of sustainable diets.